Test of insulin resistance in nondiabetic and streptozotocin-induced diabetic rats using glycosylated hemoglobin test and other interventions - Lina AlTamimi; Zainab Z Zakaraya; Mohammad Hailat; Mousa N Ahmad; Nidal A Qinna; Mohammed F Hamad; Wael Abu Dayyih (Wolters Kluwer Medknow Publications, 2024)
Type 2 diabetes is common globally. Pioglitazone (PGZ) is an oral TZD antidiabetic, whereas chromium-picolinate (Cr-PL) and Cr-glucose tolerance factor (Cr-GTF) are useful type 2 diabetes mellitus (T2DM) supplements. Cr-PL/GTF antioxidants cure T2DM. They may fail in diabetes with or without insulin-sensitizing medications. It examined how Cr-PL, Cr-GTF, PGZ, and their combination affected glucose, glycosylated hemoglobin, insulin, and HOMA-IR. Sixty-three adult Sprague-Dawley rats (220-300 g) were selected, and nine rats were randomly assigned to a normal nondiabetic group. In contrast, 54 rats were randomly split into 9 rats per each of the 6 major groups and injected intraperitoneally with 40 mg/kg STZ to induce T2DM. Rats were administered PGZ = 0.65 mg/kg (rat weight)/day, Cr-PL = 1 mg/kg, Cr-GTF = 1 mg/kg, and their combinations (PGZ + Cr-PL and Cr-GTF) daily for 6 weeks per intervention. The PGZ + Cr-PL and PGZ + Cr-GTF groups had substantially lower insulin levels than the PGZ group (13.38 ± 0.06, 12.98 ± 0.19 vs. 14.11 ± 0.02, respectively), with the PGZ + Cr-GTF group having the lowest insulin levels (12.98 ± 0.19 vs. 14.11 ± 0.02, 13.38±0.06, respectively). Intervention substantially reduced HOMA-IR in the PZ + Cr-PL and PZ + Cr-GTF groups compared to PGZ (7.49 ± 0.04, 6.69 ± 0.11 vs. 8.37 ± 0.04, respectively). This research found that combining PGZ with Cr-GTF resulted in considerably lower HOMA-IR levels than the PGZ and Cr-PL groups (6.69 ± 0.11 vs. 8.37 ± 0.04, 7.49 ± 0.04, respectively). Both Cr-PL and Cr-GTF may control T2DM. Both Cr complexes improved T2DM biomarkers more than the control diabetic group without medication. PGZ alone and PGZ + Cr-PL had less pharmacological synergy than Cr-GTF and PGZ in altering insulin and HOMA-IR blood levels. These encouraging discoveries need more study.